2024
DOI: 10.2106/jbjs.23.01013
|View full text |Cite
|
Sign up to set email alerts
|

New CMS Policy on the Mandatory Collection of Patient-Reported Outcome Measures for Total Hip and Knee Arthroplasty by 2027

Ignacio Pasqualini,
Nicolas S. Piuzzi

Abstract: The Centers for Medicare & Medicaid Services (CMS) has finalized a landmark national policy to standardize and expand the collection and reporting of patient-reported outcome measures (PROMs) following total hip arthroplasty (THA) and total knee arthroplasty (TKA). This policy will be rolled out through phased implementation, beginning with voluntary reporting starting in 2023 and transitioning to mandatory reporting starting in 2025, which will be tied to hospital payment determinations in fiscal year 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… 48 The Centers for Medicare and Medicaid Services will also begin requiring mandatory collection of PROMs in the United States in 2027. 49 In New Zealand, the New Zealand Orthopaedic Association runs a Joint Registry, which collects PROM data for hip replacement. 50 In their 2023 report, the New Zealand Orthopaedic Association found that having an Oxford Hip Score below 27 was significantly associated with undergoing a hip revision within 2 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 48 The Centers for Medicare and Medicaid Services will also begin requiring mandatory collection of PROMs in the United States in 2027. 49 In New Zealand, the New Zealand Orthopaedic Association runs a Joint Registry, which collects PROM data for hip replacement. 50 In their 2023 report, the New Zealand Orthopaedic Association found that having an Oxford Hip Score below 27 was significantly associated with undergoing a hip revision within 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…US surgeons and hospitals can report these outcomes voluntarily, and they will be required in Medicare starting in 2027. 49 The United States is also testing payment methodologies to reduce costs and potentially improve quality, but these approaches have had only small effects on reducing costs per THA case. 43…”
Section: Discussionmentioning
confidence: 99%